Creating a World Stage: Revolution Airport and the Illusion of Power. Issue 5 (2nd September 2020) - Hobson, Alex
Abstract: In 1970, at the height of the hijacking era, with resentment at Israeli occupation smoldering across the Arab world, and with Palestinian commandos poised to topple the U.S.-allied Jordanian monarchy, the Popular Front for the Liberation of Palestine (PFLP) ramped up its campaign of "external operations." While hijacking had become common, the PFLP acted on a novel conception: the establishment of a "Revolution Airport" for the performance of Palestinian power. The group claimed that this was a just and strategically valid tactic for anti-colonial armed struggle. This article examines this innovation, focusing on the event the Popular Front called "Operation Revolution Airport, " the largest mass hijacking in history, perpetrated in September 1970. The article shows how the Popular Front used performance to educate friends and foes alike, and to press the parameters of legitimate anti-colonial liberationist action, magnifying the illusion of commando power, while exposing what its leaders saw as their enemies' oppressive nature. Revolution Airport revealed the possibilities of performative violence for revolutionaries, even as it ended in a major tactical defeat for the Palestinian armed struggle.